Angel in the Rubble : The Miraculous Rescue of 9/11's Last Survivor - Guzman-McMillan, Genelle (New York : Howard Books, 2011)
Presents the story of the last survivor pulled from the debris of the World Trade Center after the terrorist attack on September 11th, and her journey from desperation to a miraculous salvation.
Keywords: World Trade Center (New York, N.Y.) -- Biography; Guzman-McMillan, Genelle; September 11 terrorist attacks, 2001 -- Biography; Terrorism -- Biography -- New York (N.Y.)